Analisis Efektifitas Pemungutan dan Pengelolaan Pajak Bumi dan Bangunan Terhadap Pendapatan Asli Daerah Kota Batam - Syari Yanti Nasution; Vargo Christian L. Tobing (Peneliti.net, 2023)
Tax is a main income of society that can be used in development. Land and Building Tax (PBB) is a fee paid for the existence of land and buildings to be able to provide benefits and socio-economic status for individuals or entities. The purpose of this study was to analyze the effectiveness of the collection and management of land and building tax on Batam City Regional Original Revenue which was carried out at the Batam City Regional Revenue Agency. The population in this study is the Batam City Regional Revenue Agency (BAPENDA) Budget Realization Report for 2017-2021. The sample in this study is the realization of local taxes and targets along with the realization of Batam City Land and Building Tax for 2017-2021. The data analysis method used in this research is descriptive qualitative analysis method as a research in producing descriptive data in the form of data collected and classified the data is then described in the data to be further described in a descriptive discussion to describe the effectiveness of the collection and management of Land and Building Tax for use increase local revenue. The results in this study indicate that the level of effectiveness of land and building tax (PBB) collection during 2017-2021 is classified as effective because based on the percentage of the effective level of collection, which averages 122.95%. And the management of Land and Building Tax (PBB) during 2017-2021 is classified as ineffective because the average percentage reaches 22.31%.